The Psychometric Properties of the Norwegian version of Infant-Toddler Social Emotional Assessment – 2. version (ITSEA) - Kornør, Hege; Olafsen, Kåre Sten (PsykTestBarn, 2011)
Description: ITSEA is a questionnaire to be completed by caregivers to identify social and emotional problems and competence in toddlers aged 12-35 months. The questionnaire contains 166 items distributed to two scales, and takes 20-30 minutes to complete. Health workers and teachers with test-related qualifications can administrate the instrument. Margaret J. Briggs-Gowan and Alice S. Carter published the original version in 2003. Norwegian translators and copyright holders are unknown. Literature search: Our systematic literature search did not identify any publications on the Norwegian version of the ITSEA. Conclusion: There is no evidence for the psychometric properties of the Norwegian version of BITSEA. It should therefore be used with great caution.